Alternative splicing determines mRNA translation initiation and function of human K2P10.1 K+ channels - Staudacher, Kathrin; Baldea, Ioana; Kisselbach, Jana; Staudacher, Ingo; Rahm, Ann-Kathrin; Schweizer, Patrick Alexander; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (The journal of physiology, 2011)
Non-technical summary The resting membrane potential of excitable cells such as neurones and cardiac myocytes depends on the distribution of potassium ions across the cell membrane. Specialized membrane proteins called K2P10.1 ion channels pass potassium ions and stabilize membranes of excitable cells at hyperpolarizing potentials below the threshold for action potential firing. Alternative mRNA translation initiation (ATI) contributes to K2P10.1 protein diversity: Ribosomal synthesis of K2P10.1 channel proteins harbouring different N-terminal domains initiated from two downstream mRNA start codons regulates K2P10.1 function. We now demonstrate that splicing determines translation start sites of human K2P10.1 mRNA via recombination of short nucleotide signalling sequences preceding the first start mRNA codon, revealing a novel biological mechanism. Our study suggests that tissue-specific K2P10.1 ion channel mRNA splicing and translation initiation determines the resting membrane potential and contributes to electrophysiological plasticity of neuronal and cardiac cells.
Im Titel ist der Ausdruck "2P" tiefgestellt
Im Titel ist das Pluszeichen hochgestellt
Gesehen am 20.10.2022